PELATIHAN TATA KELOLA PENYEMBELIHAN HALAL DAN THOYYIB DI MUSHOLA AL-IKHLASH KECAMATAN CIBUGEL, SUMEDANG - Purnama Putra; Yoyo Hambali; Akmal Rizki Hasibuan; Musyafa Amin Ash Shabah4; Rafika Rahmawati; Acep Mulyadi; Suprihatin Suprihatin; Siti Asiah; Agus Supriyanto (DEVOSI, 2023)
Idhul Adha is a holiday for Muslims around the world where on that day there is an activity, namely the slaughter of sacrificial animals, but there are issues and focuses that are faced first, the lack of knowledge of the general public about halal slaughter, second, namely the management of packaging and processing Qurbani meat. Community Service at the Faculty of Islamic Religion focuses on Eid al-Adha/qurban governance, especially in the management of sacrificial animals starting from slaughtering to packaging and processing of the meat. Community service activities related to halal slaughter training and qurban meat packaging and processing governance aim to improve skills and knowledge about halal slaughtering and management of qurban meat packaging and processing for the Sukaraja Village Community and the Management of the Al-ikhlas Mushala RT.06/RW.02. The Community Service Team of the Faculty of Islamic Religion, Islamic University 45 (UNISMA) uses the training method. This activity was carried out offline by providing descriptions and examples indoors for the next stage to be practiced together with the residents of the Al-ikhlas Cibugel Mosque, Sumedang. The results of the implementation of community service activities which were manifested in the form of training on the slaughter and processing of halal and thoyyib sacrificial animals for the management of the Al-Ikhlas Mosque in Cibugel, Sumedang as a whole ran smoothly and were able to increase public understanding. This is evidenced by the enthusiasm, active involvement, contentment in the discussions and practices of most of the management. Another impact that the community received from this activity was in the form of increasing the community's sense of belonging to their religion and nation, dividing some of the qurbani meat, increasing community sensitivity and the spirit of mutual cooperation which in Sundanese terms is known as the concept of sabilulungan.